Resolution of Complete AV block to Normal Sinus Rhythm without Cardiac Pacemaker in a Patient with Severe Acidosis: A Case Report - Filiana, Rari Dewinda Sudarmaji; Kusuma, Taufik Ridwan Hadi; Noviar, Vira Khairunisa (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2024)
Background : Complete atrioventricular block (CAVB) is a life-threatening medical emergency and requires an immediate cardiac pacemaker to reduce mortality by up to 87%.Case Illustration : A 55-year-old woman with an unknown medical history was brought to the emergency room with a Glasgow Coma Scale (GCS) of E2V1M1 (sopor comatose) and Kussmaul breathing. The patient, who was in septic shock, had Multiple Organ Dysfunction Syndrome (MODS) and severe acidosis. The patient was hemodynamically unstable, requiring vasopressor to maintain a Mean Arterial Pressure (MAP) ≥ 65 mm Hg. The analysis of the arterial blood gas revealed a pH of 7.19, pCO2 of 16 mm Hg, pO2 of 204 mm Hg, and bicarbonate of 5.9 mmol/L. Hyperkalemia (5.33mmol/L) was discovered during the electrolyte analysis. Conclusion : An electrocardiogram (ECG) examination showed CAVB with non-malignant ventricular extrasystoles. Without the use of a cardiac pacemaker, the ECG becomes normal sinus rhythm after corrections for severe acidosis and hyperkalemia. This case demonstrates that severe acidosis and hyperkalemia can induce reversible CAVB without the use of a pacemaker. Hence, it should be evaluated as part of the initial assessment and therapy of CAVB before a cardiac pacemaker is implanted.